A planning tool for maximising transit services. Issue 1 (2nd January 2016) - Ma, Yunfeng; Li, Jianling; Han, Chien-Pai
Abstract : Transit is important for urban sustainable development, but the cost of providing transit services is high. Strategic planning for a public transit system is necessary to maximise the return of public investment. We develop a planning tool to aid decision-making about service area, using optimisation techniques for the Prize-Collecting Salesman problem and the concept of hierarchy of travel needs. We demonstrate the usefulness of the model for maximising service area under a given budget constraint and socioeconomic conditions, and suggest future research directions.